MOLECULAR IDENTIFICATION OF CTX GENE OF EXTENDED SPECTRUM BETA-LACTAMASES (ESBL) PRODUCING ESCHERICHIA COLI ON LAYER CHICKEN IN BLITAR, INDONESIA - F. J. Wibisono; B. Sumiarto; T. Untari; M. H. Effendi; 5; D. A. Permatasari; A. M. Witaningrum (Journal of Animal and Plant Sciences, 2020)
Escherichia coli is one of the ESBL-producing bacteria responsible for the rise of antibiotic resistance. The most common type of ESBL-encoding gene is cefotaximase (CTX). The aim of study was to identify CTX-encoding gene among Escherichia coli on Layer Chicken in Blitar, Indonesia by using DNA-based techniques. To do this, a total of 130 swab cloacal samples were randomly collected from layer chicken in 4 districts of Blitar. Samples was initially cultured on MacConkey agar and Eosin Methyllen blue agar. Subsequently, the suspected isolates were identified in TSIA test and IMVIC biochemistry test. The method of Confirmation test ESBL-producing Escherichia coli was performed by Double Disc Synergy Test (DDST), and the final characterization of the isolates were conducted using VITEK® 2 Compact. Following that, the identified isolates were exposed to PCR amplification for the presence of CTX gene in ESBL-producing Escherichia coli, followed by the visualization of the amplicons in the electrophoresis. Overall, the results was showed that 80% of the ESBL-positive isolates contained CTX gene. In conclusion, this report the high frequency of CTX gene in ESBL producing Escherichia coli, and thereby posing a significant threat for the animal and human health.
Keywords: CTX gene; ESBL; Escherichia coli; Human health; PCR; VITEK®